2022
DOI: 10.1021/acsomega.1c05995
|View full text |Cite
|
Sign up to set email alerts
|

Permeability Loss of Bituminous Coal Induced by Water and Salinity Sensitivities: Implications of Minerals’ Occurrence and Pore Structure Complexity

Abstract: Water sensitivity (WS) and salinity sensitivity (SS) are key issues to be investigated for instructing coalbed methane (CBM) production. This work studied the influences of minerals and pores on WS and SS of medium-volatile bituminous coal (MVBC) and highly volatile bituminous coal (HVBC) deposited in northwestern China by detecting and observing minerals using the TESCAN Integrated Mineral Analyzer, simulating WS and SS, and characterizing pore structural complexities using rate-controlled mercury penetration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It has been reported that the reservoir permeability and production rate decrease with the stress sensitivity coefficient for both coal seams and shale reservoirs, and the stress sensitivity coefficient reduces with the increasing effective stress. ,,, In other words, the increase of effective stress results in compaction of cleats, making cleats more resistant to compaction force, and the stress sensitivity coefficient drops, as proven by a number of experimental data (e.g., Figure ). , Studies have also revealed that (i) temperature and moisture content can enhance the stress sensitivity, (ii) the stress sensitivity decreases with the pore/fracture aperture and can be affected by fracture morphology, , and (iii) the stress sensitivity coefficient show strong anisotropy with a higher value typically in the horizontal direction. ,, Zhang et al proposed that the new fractures generated from shear and tensile failure in coal exert an evident impact on stress sensitivity, which matched with the results obtained by Tan and Konietzky . It is clear that the stress sensitivity coefficient constantly varies during production, so it is vital to quantify its variation to reliably estimate coal permeability evolution during the dewatering as well as gas production stages.…”
Section: Affecting Factors Of Dewatering Rate Optimizationmentioning
confidence: 56%
“…It has been reported that the reservoir permeability and production rate decrease with the stress sensitivity coefficient for both coal seams and shale reservoirs, and the stress sensitivity coefficient reduces with the increasing effective stress. ,,, In other words, the increase of effective stress results in compaction of cleats, making cleats more resistant to compaction force, and the stress sensitivity coefficient drops, as proven by a number of experimental data (e.g., Figure ). , Studies have also revealed that (i) temperature and moisture content can enhance the stress sensitivity, (ii) the stress sensitivity decreases with the pore/fracture aperture and can be affected by fracture morphology, , and (iii) the stress sensitivity coefficient show strong anisotropy with a higher value typically in the horizontal direction. ,, Zhang et al proposed that the new fractures generated from shear and tensile failure in coal exert an evident impact on stress sensitivity, which matched with the results obtained by Tan and Konietzky . It is clear that the stress sensitivity coefficient constantly varies during production, so it is vital to quantify its variation to reliably estimate coal permeability evolution during the dewatering as well as gas production stages.…”
Section: Affecting Factors Of Dewatering Rate Optimizationmentioning
confidence: 56%
“…Additionally, the pores and structure of clay minerals are damaged by water swelling, collapsibility, and the water lock effect caused by water sensitivity. Specifically, the hydration and expansion of clay minerals may produce particle migration, which lead to the decline of reservoir porosity and permeability, and irreversible damage to the pore system of reservoir. Collapsibility may lead to pore throat blockage, and poor porosity and permeability. Also, the water lock effect caused by the increase of reservoir water saturation reduces the reservoir permeability. , In addition, it is not conducive to the formation and distribution of three-dimensional fracture networks in the reservoir fracturing process. The interaction mechanism between water and clay minerals is extremely complex. So far, the damage mechanism of clay pore structure and the control mechanism of competitive adsorption of water and CH 4 have not been determined.…”
Section: Influence Of Clay Content On Ch4 Adsorption Capacity In a Sh...mentioning
confidence: 99%
“…Initially, kaolinite particles detach from the mesopores or transition pores and migrate toward the narrow throats of macropores and super-macropores. This migration pattern results in volume reduction of macropores and super-macropores, ultimately leading to a loss of permeability . Although numerous research results on the influence of hydrochemical properties on the migration of coal fines have been reported, there are few studies on the migration law of coal fines containing kaolinite in propped fractures under different hydrochemical properties.…”
Section: Introductionmentioning
confidence: 99%